2016
DOI: 10.1111/jace.14393
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Processing Parameters on the Deposition of Yttria Partially Stabilized Zirconia Coating During Suspension Plasma Spray

Abstract: The process–microstructure relationship in suspension plasma spray (SPS) of yttria partially stabilized zirconia (YSZ) has been studied experimentally. An ethanol‐based suspension with a powder loading of 25 wt% was plasma sprayed with radial injection under four different plasma conditions, to examine the effects of plasma gas composition (Ar/He ratio), secondary gas (Ar/He and Ar/H2), and the nozzle diameter of the plasma gun. The suspension feeding rate was optimized firstly and coatings were prepared for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 45 publications
(124 reference statements)
0
8
0
Order By: Relevance
“…The advantage of this technic called SPS (Suspensions Plasma Spraying) is to be able to elaborate very thin layers with various microstructures: columnar, dense, homogeneous, feathery… (Ref [25][26][27][28][29][30][31]. This microstructure depends on many parameters such as suspension load, suspension feed rate or substrate roughness (Ref [25][26][27][28]30). Seshadri et al (Ref 26) also recently showed that characteristics of the plasma flow, i.e., total gas flow rate and torch net power could affect coating microstructures in SPS.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of this technic called SPS (Suspensions Plasma Spraying) is to be able to elaborate very thin layers with various microstructures: columnar, dense, homogeneous, feathery… (Ref [25][26][27][28][29][30][31]. This microstructure depends on many parameters such as suspension load, suspension feed rate or substrate roughness (Ref [25][26][27][28]30). Seshadri et al (Ref 26) also recently showed that characteristics of the plasma flow, i.e., total gas flow rate and torch net power could affect coating microstructures in SPS.…”
Section: Introductionmentioning
confidence: 99%
“…For example, yttria‐stabilized zirconia (YSZ) coatings, one of the most widely utilized thermal barriers, are frequently applied to target substrates via thermal plasma spray processes. [ 14–16 ] These processes expose the target substrate to molten particles or high‐temperature precursors throughout coating formation. As the temperatures required to synthesize YSZ as well as to convert particles to a molten state are exceedingly high (i.e., higher than the intended exposure temperature of the substrate), these processes can thermally damage the top layer of the substrate (often a bond coat).…”
Section: Introductionmentioning
confidence: 99%
“…Many variables, such as pH, solid loading, dispersant, and media affecting the surface properties of YSZ particles have been investigated. 3,4 Electrostatic and electrosteric stabilization are the two well-known mechanisms which are used for the dispersion of particles. Electrostatic charging acts through the adsorption of ions on the surfaces of particles.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to stabilize the YSZ suspension, study its rheological behavior, and investigate the suspension repeatability properties. Many variables, such as pH, solid loading, dispersant, and media affecting the surface properties of YSZ particles have been investigated 3,4 …”
Section: Introductionmentioning
confidence: 99%